2014
DOI: 10.1038/ijo.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in young children: definitions and results of the IDEFICS study

Abstract: on behalf of the IDEFICS consortium OBJECTIVE: To estimate the prevalence of the metabolic syndrome (MetS) using reference standards obtained in European children and to develop a quantitative MetS score and describe its distribution in children. DESIGN AND METHODS: Population-based survey in eight European countries, including 18 745 children 2.0 to 10.9 years, recruited during a second survey. Anthropometry (weight, height and waist circumference), blood pressure and serum-fasting triglycerides, HDL choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
274
2
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(314 citation statements)
references
References 51 publications
14
274
2
18
Order By: Relevance
“…In accordance, studies have shown a high prevalence of MetS, not only in pubertal but also in prepubertal obese children [127,128].…”
Section: Metabolic Syndromesupporting
confidence: 53%
“…In accordance, studies have shown a high prevalence of MetS, not only in pubertal but also in prepubertal obese children [127,128].…”
Section: Metabolic Syndromesupporting
confidence: 53%
“…Fasting blood was collected either by venipuncture or by capillary sampling as described in detail in Ahrens et al [25]. To ensure that basic data on metabolic disorders were available for as many children as possible a point-of-care analyser (Cholestech LDX, Cholestech Corp.) was used to assess blood glucose, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol and triglycerides.…”
Section: Blood Collectionmentioning
confidence: 99%
“…We anticipate that if an equivalent (to adult) definition of MHO is used, the prevalence of MHO in youth will be higher than in adults because children and adolescents are expected to be healthier and metabolic abnormalities are known to increase with age. Several large-scale studies in youth have examined the prevalence of MetS (using different definitions) in children and adolescents in the United States [95][96][97] and Europe 98,99 ; however, the prevalence of MHO was not provided nor could be calculated from the data reported.…”
Section: Ortega Et Al Obesity and Cardiovascular Disease 1761mentioning
confidence: 99%